EFL Students’ Experience in Distance Learning during COVID-19 from a Multidimensional Transactional Distance Perspective - Murad Abdu Saeed; Su Kia, Lau; Ahmed Ali Mahdi; Almaamari, Ahmed Ali (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Emergence learning during the COVID-19 pandemic was a challenging experience for many learners possibly due to the physical and psychological distance. This distance conceptualized as a transactional distance according to Moore’s theory is a critical issue in distance learning. Therefore, the present study attempted to (1) determine Saudi EFL students’ levels of perceived transactional distance in distance learning, (2) measure the impact of the interaction of course structure, dialogue and learner autonomy on Saudi EFL students’ perceived TD in distance learning during the COVID-19 pandemic (3) examine the effect of socio-demographic and environmental factors on their perceived transactional distance. By administering a multidimensional electronic (e-)survey to 189 students joining distance learning in a Saudi public university, the study provided evidence of learners’ high levels of perceived dialogue, structure, and autonomy, along with low levels of perceived transactional distance. The correlation analyses showed that dialogue, structure, and learner autonomy significantly and inversely correlate with learners’ transactional distance. The ANOVA analysis revealed that the interaction of dialogue and course structure significantly impacts the perceived transactional distance. Moreover, learners’ levels of perceived transactional distance varied according to their socio-demographic and environmental factors, specifically age, gender, university discipline/major and number of online courses taken by them. The study provides useful pedagogical implications for technology use in sustaining learners’ online learning experiences in terms of dialogue, structure and autonomy and in reducing their perceived transactional distance. Thus, the study is useful for promotion of the distance learning potentials in higher educational institutions.